2015
DOI: 10.1109/jsee.2015.00001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic channel reservation scheme based on priorities in LEO satellite systems

Abstract: According to low earth orbit (LEO) satellite systems with users of different levels, a dynamic channel reservation scheme based on priorities is proposed. Dynamic calculation of the thresholds for reserved channels is the key of this strategy. In order to obtain the optimal thresholds, the traf c is predicted based on the high-speed deterministic movement property of LEO satellites rstly. Then, a channel allocation model based on Markov is established. Finally, the solution of the model is obtained based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Accordingly, we define the user satisfaction score following [14] as where r and p are the handover success reward score and the handover failure penalty score, respectively, and T latency is given by (4). In our simulation, we set r = 1 and p = 0.1 [14].…”
Section: B Quality Of Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, we define the user satisfaction score following [14] as where r and p are the handover success reward score and the handover failure penalty score, respectively, and T latency is given by (4). In our simulation, we set r = 1 and p = 0.1 [14].…”
Section: B Quality Of Experiencementioning
confidence: 99%
“…This is similar to the network-initiated and network-controlled hard handover in long-term evolution (LTE) systems [3], where the base stations make hard handover decisions in order to route data packets correctly. There have also been lots of academic research efforts studying resource management and handover schemes in satellite networks [4]- [6]. It has been shown that the centralized algorithm [4] and hybrid handover schemes [5] can improve the overall quality of service (QoS) during handover.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By anticipating the user motion and reserving resources, DDBHP estimates the residence time of the user in each cell to be crossed and reserves a resource during the corresponding residence time interval. Similarly, other solutions have been provided to delay the channel locking in the next candidate cell and trade-off the handover guarantee to a certain extent: The Elastic Channel Locking scheme [5], Time-based Channel Reservation Algorithm method [6] [7], Threshold-Based Handover Prioritization scheme [8], Channel Status based Reservation Strategy [9], Dynamic Channel Reservation scheme based on Priorities [10], and a geographical information based resource reservation algorithm [11].…”
Section: Introductionmentioning
confidence: 99%
“…To guarantee a certain QoS to handover calls, a fixed channel reservation (FCR) policy is considered, named channel-locking mechanism, that treats different the first handover from the subsequent handovers of a call. Extensions of [4] are related to schemes based on: i) dynamic channel reservation with [5] or without priorities [6], ii) time-based channel reservation [7], [8] iii) Doppler-based handover prioritization [9], [10], iv) probabilistic reservation for the handover management [11] and v) FCR with first-infirst-out queuing handover [12]. Recently, in [13] a queuing model has been proposed for the analysis of a LEO-MSS in the case of correlated service times.…”
mentioning
confidence: 99%